ПОСЛЕДОВАТЕЛЬНОСТЬ, ОСОБЕННОСТИ И ФАКТОРЫ ПЕДАГОГИЧЕСКОГО ИССЛЕДОВАНИЯ ВОСПИТАТЕЛЬНЫХ РАБОТ В НАШЕЙ СТРАНЕ - Бекетов, Н.А. (SCIENCE and SOCIETY, 2022)
This article considers that the improvement of the educational process in schools is a continuous process in accordance with the laws of the development of dialectics.